Persepsi Mahasiswa Generasi Z terhadap Tantangan Finansial dan Akademik dalam Kuliah Sambil Bekerja : (Studi Kasus Mahasiswa STIES Putra Bangsa Tegal Angkatan 2022) - Isnaeni Zahrotun Maulidiyah (Jurnal Publikasi Sistem Informasi dan Manajemen Bisnis, 2025)
The dynamics of today's digital economy have driven many Generation Z students to take on dual roles as learners and income earners. This reality presents significant challenges, particularly in managing financial constraints and academic workload. This study aims to explore how Generation Z students perceive and respond to financial and academic pressures while balancing work and university commitments. A qualitative approach was applied using a structured questionnaire composed of open- and close-ended items distributed to active student-workers. The theoretical foundation is grounded in Peter Drucker's concept of self-management and Stephen Covey’s principles of time and priority management. The findings indicate that most students experience difficulty maintaining financial stability and academic performance. However, many demonstrate adaptive behavior in organizing their schedules, setting priorities, and applying self-management strategies independently. These results underscore the need for universities to provide time-management training and personal development support. This research contributes to shaping more flexible educational policies and support systems tailored to the needs of working students.